2014
DOI: 10.2147/ijn.s67770
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin-modified nanostructured lipid carriers as multifunctional nanomedicine for codelivery of DNA and doxorubicin

Abstract: Background Nanostructured lipid carriers (NLC), composed of solid and liquid lipids, and surfactants are potentially good colloidal drug carriers. The aim of this study was to develop surface-modified NLC as multifunctional nanomedicine for codelivery of enhanced green fluorescence protein plasmid (pEGFP) and doxorubicin (DOX). Methods Two different nanocarriers: pEGFP- and DOX-loaded NLC, and solid lipid nanoparticles (SLN) were prepared. Transferrin-containing ligands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Remarkable tumor inhibition in TF-HA- CMC-PLGA NPs group indicated that the potential superiority of TDDS. We concluded the different PDT efficacy in vivo that nanocarrier could improve the water-solubility and bioavailability of HA and TFR-mediated endocytic pathway could improve the cellular uptake of TF-modified nanoparticles within TFR positive cancer cells (Han et al, 2014 ; Guo et al, 2017 ). Body weight of mice reflects the health condition, so it is an indispensable factor to monitor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Remarkable tumor inhibition in TF-HA- CMC-PLGA NPs group indicated that the potential superiority of TDDS. We concluded the different PDT efficacy in vivo that nanocarrier could improve the water-solubility and bioavailability of HA and TFR-mediated endocytic pathway could improve the cellular uptake of TF-modified nanoparticles within TFR positive cancer cells (Han et al, 2014 ; Guo et al, 2017 ). Body weight of mice reflects the health condition, so it is an indispensable factor to monitor.…”
Section: Resultsmentioning
confidence: 99%
“…The strategy of utilizing TF/TFR as a drug targeting carrier is based on the overexpression of TFR on the surface of tumor cells. Han et al have reported that a TF-modified multifunctional nanomedicine noticeably enhanced antitumor activity and improved the lung cancer cell-targeting in a mouse bearing A549 cells model (Han et al, 2014 ). Based on this premise, we designed a TDDS which had an active targeted ligand and could promote the water-solubility of HA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GEE of NCs was determined by PicoGreen ® fluorometry assay. 28 It was calculated according to the linear calibration curve of pEGFP, according to the equation: (weight of total pEGFP - free pEGFP)/(weight of total pEGFP)×100.…”
Section: Methodsmentioning
confidence: 99%
“…8 These carriers include polymeric nanoparticles, liposomes, micelles, dendrimers, and so on. 9 The application of nanocarriers in the treatment of HCC is timely and has been recently reviewed. 10 Nanocarriers can be modified with specific ligands which can assist in targeting and internalization of the drugs to specific cell populations, such as cancer cells.…”
Section: Introductionmentioning
confidence: 99%